ASSESSMENT OF THE CONTRIBUTION OF THE INVESTMENT POTENTIAL TO INCREASING THE EFFICIENCY OF AGRICULTURAL PRODUCTION - Marianna VASILCHENKO; Elena DERUNOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the context of the transition to a new technological structure and the formation of an export-oriented economy, the achievement of sustainable agricultural development is inextricably linked with the search for new forms, methods, and mechanisms to stimulate the development of the investment potential of agricultural production. The study aims to assess the contribution of investment potential to improving the efficiency of agricultural production and to develop innovative policy measures to stimulate its development. The theoretical aspects of the development of investment potential have been developed. The role of foreign investment in agriculture in increasing the productivity of the industry and meeting the needs of the industry for various resources has been substantiated. The specificity of the provision of investment resources in agriculture has been studied. An empirical assessment of the multiplier effect of investments was carried out using a pool of indicators. Based on the proposed private indicators, an integral indicator for assessing the effectiveness of the investment potential of agricultural production was calculated. A typology of the constituent entities of the Russian Federation has been carried out on the contribution of investment potential to innovative development and growth of export potential; groups with a low, medium and high level of development are identified. The article proposes measures to stimulate innovative development based on expanding the forms of interaction and methods of investment policy, science, and agribusiness in the context of framework conditions, project, and institutional measures. The practical significance of the results of the study is to improve the methodology for assessing the level of development of investment potential and increase the efficiency of agricultural production based on improving government support measures at all stages of the innovation process.